Policy Analysis of Budget Allocation for Disasters in Indonesia - Hari Apryana; Karina Rahma Nugraheni; Fatimah Wardhana (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
As a country with high vulnerability to natural disaster, the government and communities must be prepared for disasters threats that may occur at any time. One of the most important aspects in disaster management is budgeting, which can support the effectiveness of the sustainable management. The source of disaster funding comes from the State Budget (APBN) as stated in PP. 22/2008 Article 4 paragraph (2). One of the APBN funds provided by the government is in the form of contingency funds. This study aims to analyze the implementation of disaster management preparedness funding policies and examine the problems of disaster management in the aspect of coordination among institutions. This research is a policy research conducted using a descriptive qualitative approach and literature review. The results showed that there is an overlap between budget policies and coordination among institutions in the calculation of the budget for disaster preparedness funding.